The technological transformation of the Russian energy sector forced by carbon regulation - A. V. Shigina; A. A. Khorshev (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE of the study lies in the assessment of the impact that various carbon regulation instruments stimulating the achievement of national climate goals have on the development scale of different electricity and heat production technologies in Russia.THE PURPOSE. To consider the change in the optimal technological structure of the electric power industry and district heating in Russia by 2050 assuming the introduction of various carbon regulation instruments in 2030.METHODS. We used the developed at ERI RAS system technological model EPOS for the optimization of the energy technology structure in the Russian energy sector according to the criterion of the minimum total discounted costs for energy supply to the economy until 2050.RESULTS. The article provides an analysis of the scale of changes in installed capacity and electricity production of various types of power plants in the UES of Russia, as well as changes in heat production of different heat supply sources by 2050 for 16 carbon regulation options and business-as-usual scenario. Also it describes the optimal technological structure in the electric power industry and district heating under the conditions of certain administrative, fiscal and economic instruments of climate policy. Carbon regulation options based on the corresponding increases in the installed capacity of power plants in the UES of Russia by 2050 are compared.CONCLUSION. Decarbonization of the electric power industry in Russia will mainly occur by expansion of nuclear energy, heat production – by deployment of electric boilers, taking into account current forecasts of scientific and technological progress. At the same time, for carbon regulation options leading to a greenhouse gas emissions reduction by 30% relative to 2019 level, nuclear power plants could become the new dominant technology in the structure of electricity production instead of gas thermal power plants. The total increase in installed capacity of power plants in the UES of Russia by 2050 may differ by almost seven times for various carbon regulation options. Among the climate policy options considered, emission quotation and carbon taxes have the strongest impact on the technological structure of the electric power industry and district heating in Russia.